2016
DOI: 10.1007/s12016-016-8589-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Extracellular MicroRNA in Respiratory Diseases

Abstract: Lack of markers of subclinical disease state and clinical phenotype other than pulmonary function test has made the diagnosis and interventions of environmental respiratory diseases a major challenge. MicroRNAs (miRNAs), small non-coding single stranded RNAs, have emerged as potential disease-modifier in various environmental respiratory diseases. They can also be found in various body fluids and are remarkably stable. Because of their high stability, disease-specific expression, and the ease to detect and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 68 publications
0
43
0
1
Order By: Relevance
“…In addition, studies showed that also other population characteristics such as age, weight, smoking status, and ethnicity can affect the identification of miRNA markers . Even other benign diseases such as chronic obstructive pulmonary disease (COPD), asthma, and tuberculosis can alter blood miRNA profiles and make some study participants unsuitable controls . Therefore, in this systematic review, we selected Western populations and excluded studies with disease controls to reduce the heterogeneity of included miRNAs caused by above‐mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies showed that also other population characteristics such as age, weight, smoking status, and ethnicity can affect the identification of miRNA markers . Even other benign diseases such as chronic obstructive pulmonary disease (COPD), asthma, and tuberculosis can alter blood miRNA profiles and make some study participants unsuitable controls . Therefore, in this systematic review, we selected Western populations and excluded studies with disease controls to reduce the heterogeneity of included miRNAs caused by above‐mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…12,[34][35][36] Even other benign diseases such as chronic obstructive pulmonary disease (COPD), asthma, and tuberculosis can alter blood miRNA profiles and make some study participants unsuitable controls. [37][38][39] Therefore, in this systematic review, we selected Western populations and excluded studies with disease controls to reduce the heterogeneity of included miRNAs caused by above-mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are small noncoding RNAs that control gene expression posttranscriptionally by inhibiting translation, and thus, they play a central role in the epigenetic modification of gene expression. In addition, their promising potential as biomarkers and basis for the development of new classes of therapeutic compounds has been described recently [103,104].…”
Section: New Research Fieldsmentioning
confidence: 99%
“…On the one hand, extracellular miRNAs hold great potential to act as disease biomarkers due to their non‐invasive accessibility and remarkable stability . A great number of studies have shown that miRNAs are differently enriched in MVs, and their expression patterns also change with respect to different diseases . Therefore, MVs and associated miRNAs are considered to be potential diagnostic biomarkers of diseases .…”
Section: Existing Problems Of Mvs and The Clinical Prospectsmentioning
confidence: 99%
“…60,77,129 A great number of studies have shown that miRNAs are differently enriched in MVs, and their expression patterns also change with respect to different diseases. 130 Therefore, MVs and associated miRNAs are considered to be potential diagnostic biomarkers of diseases. [131][132][133] For instance, in a prospective study, in 176 patients with stable coronary artery disease (CAD), Jansen F at al.…”
Section: The Clinical Prospect Of Mvsmentioning
confidence: 99%